Structural and functional characterization of BnSP-7, a Lys49 myotoxic phospholipase A(2) homologue from Bothrops neuwiedi pauloensis Venom - Soares, A. M.; Guerra-Sa, R.; Borja-Oliveira, C. R.; Rodrigues, V. M.; Rodrigues-Simioni, L.; Rodrigues, V; Fontes, MRM; Lomonte, B.; Gutierrez, J. M.; Giglio, JR (Academic Press Inc., 2000)
BnSP-7, a Lys49 myotoxic phospholipase A, homologue from Bothrops neuwiedi pauloensis venom, was structurally and functionally characterized. Several biological activities were assayed and compared with those of the chemically modified toxin involving specific amino acid residues, the cDNA produced from the total RNA by RT-PCR contained approximately 400 bp which codified its 121 amino acid residues with a calculated pi and molecular weight of 8.9 and 13,727, respectively. Its amino acid sequence showed strong similarities with several Lys49 phospholipase A, homologues from other Bothrops sp, venoms. By affinity chromatography and gel diffusion, it was demonstrated that heparin formed a complex with BnSP-7, held at least in part by electrostatic interactions. BnSP-7 displayed bactericidal activity and promoted the blockage of the neuromuscular contraction of the chick, biventer cervicis muscle. In addition to its in vivo myotoxic and edema-inducing activity, it disrupted artificial membranes, Both BnSP-7 and the crude venom released creatine kinase from the mouse gastrocnemius muscle and induced the development of a dose-dependent edema. His, Tyr, and Lys residues of the toxin were chemically modified by 4-bromophhenacyl bromide (BPB), 2-nitrobenzenesulfonyl fluoride (NBSF), and acetic anhydride (AA), respectively. Cleavage of its N-terminal octapeptide was achieved with cyanogen bromide (CNBr), the bactericidal action of BnSP-7 on Escherichia coli was almost completely abolished by acetylation or cleavage of the N-terminal octapeptide, the neuromuscular effect induced by BnSP-7 was completely inhibited by heparin, BPB, acetylation, and CNBr treatment. The creatine kinase releasing and edema-inducing effects were partially inhibited by heparin or modification by BPB and almost completely abolished by acetylation or cleavage of the N-terminal octapeptide, the rupture of liposomes by BnSP-7 and crude venom was dose and temperature dependent. Incubation of BnSP-7 with EDTA did not change this effect, suggesting a Ca2+-independent membrane lytic activity. BnSP-7 cross-reacted with antibodies raised against B. moojeni (MjTX-II), B. jararacussu (BthTX-I), and B. asper (Basp-II) myotoxins as well as against the C-terminal peptide (residues 115-129) from Basp-II. (C) 2000 Academic Press.
Keywords: snake venom; Bothrops neuwiedi; phospholipase A(2); myotoxin; cDNA cloning; bactericidal action; neurotoxicity; chemical modification